Geology and geochemistry of metabasic rocks from aÇungui supergroup, north of quarenta oitava shear zone, south of sÃo paulo state - Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Godoy, Antonio Misson [UNESP]; Luvizotto, George Luiz [UNESP]; Zenero, Jonas Menezes [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Basic and ultrabasic ortho-derived rocks are composed of amphibolites, metabasites and metaultrabasites of meso to neoproterozoic age, are located in the southwest of São Paulo State, in Ribeira Belt southern portion and north of Apiaí Terrain. They are inserted in Supergroup Açungui metavolcanicsedimentary rocks, specifically in Água Clara Formation and Itaiacoca Group The main mineral paragenesis consists of ferrotschermakite- ferrohornblende- magnesiohornblende ± oligoclase andesine, representing the progressive regional metamorphism M1 climax, from 611 °C to 621 °C in temperature and 6.5 kbar to 7.3 kbar (± 0, 6) (Mid amphibolite facies); and a mineral paragenesis of actinolite tremolite ± albite, from M3 regional retrometamorphism (low to mid greenschist facies). Compositional geochemical data classify the rocks as gabbro, basanite and picrite, low potassium sub alkaline to alkaline, Fe-tholeitic to Mg-tholeitic, with a slight tendency to komatiitic basalts. Geotectonic data, corroborated by the behavior of trace elements and REEs, indicate three main signatures for amphibolitic groups: Basic tholeitic and komatiitic rocks associated with mid-ocean ridge (MORB), with possible crust interaction in subduction phase; ultrabasic alkaline ocean island rocks (OIA); and island arc tholeiitic basalts. Therefore, magmatism is correlated to the initial stage of opening of the basin or to the beginning of closure, to the initial phase of tholeitic ocean floor nature, associated with ocean island alkaline basalts.
Geologia E Geoquímica Das Rochas Metabásicas Do Supergrupo Açungui A Norte Da Zona De Cisalhamento Quarenta Oitava, Sul Do Estado De São Paulo
Keywords: Açungui Supergroup; Geochemistry; Geology; Metabasic